Vaccinia Virus Infection in Monkeys, Brazilian Amazon - Jônatas S. Abrahão; André T. Silva-Fernandes; Larissa S. Lima; Rafael K. Campos; Maria I.M.C. Guedes; Marcela M.G. Cota; Felipe L. Assis; Iara A. Borges; Milton F. Souza-Júnior; Zélia I.P. Lobato; Cláudio A. Bonjardim; Paulo C.P. Ferreira; et al. (Emerging Infectious Diseases, 2010)
To detect orthopoxvirus in the Brazilian Amazon, we conducted a serosurvey of 344 wild animals. Neutralizing antibodies against orthopoxvirus were detected by plaque-reduction neutralizing tests in 84 serum samples. Amplicons from 6 monkey samples were sequenced. These amplicons identified vaccinia virus genetically similar to strains from bovine vaccinia outbreaks in Brazil.